The River at the End of the World: Architectural Coexistence Along the Klamath River - Hagan, Peter James (My University, 2025)
This thesis explores the history of the Klamath River and the ever-changing landscape that it shapes and by which its path is determined. In late 2024, four out of the five dams blocking the Klamath River were removed allowing the river to return to its historical routes, opening pathways for migration and allowing the river to express natural behavior that can be observed through six different landscape sites: the spring, the floodplain, the ravine, the valley, the confluence, and the delta. Today, as the river begins to distinguish its course through the landscape once again unimpeded, this project proposes interventions within these six distinct landscapes to allow for the witnessing of these characteristics of the river to reconnect with the cycles of water and wetness, and to think of new ways of observing and engaging with the realities of changing landscape. This thesis focuses on two sites in particular: the ravine and the delta. At the ravine a bridge is proposed to span the river at the site of a former train bridge crossing. From the bridge a tower is constructed to mark the changes in water level during and after the presence of the dams. At the delta site a series of walls are proposed, which structures are built, to help visitors observe the uncertainty of a landscape that is in constant change. Together, along with the six other sites, these two proposals constitute a different kind of relationship architecture may have with water and landscape.
Thesis (Master's)--University of Washington, 2025
Keywords: Architecture; Dams; Klamath; River; Architecture; Architecture